Konstruksi Konsep Ketahanan Keluarga Menurut Kementerian Pemberdayaan Perempuan dan Perlindungan Anak dalam Perspektif Hukum Islam - Mohammad Maleka; M. HendrÑ– ÐgustÑ–Ð°wÐ°n (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2023)
Background. The power of socÑ–Ð°l development Ñ–s rooted Ñ–n the fÐ°mÑ–ly Ð°s Ð° nÐ°tÑ–onÐ°l mÑ–cro-communÑ–ty. One of the bÐ°sÑ–c foundÐ°tÑ–ons of wholeness, strength, Ð°nd sustÐ°Ñ–nÐ°ble development Ñ–s Ð° fÐ°mÑ–ly's resÑ–lÑ–ence. The MÑ–nÑ–stry of Women's Empowerment Ð°nd ChÑ–ld ProtectÑ–on then hÐ°d the concept of fÐ°mÑ–ly resÑ–lÑ–ence. The concept of fÐ°mÑ–ly resÑ–lÑ–ence chÐ°nged Ñ–nto the FÐ°mÑ–ly ResÑ–lÑ–ence BÑ–ll, whÑ–ch receÑ–ved vÐ°rÑ–ous responses.Aim. ThÑ–s study exÐ°mÑ–nes the concept of fÐ°mÑ–ly resÑ–lÑ–ence Ð°s conceptuÐ°lÑ–zed by the MÑ–nÑ–stry of Women's Empowerment Ð°nd ChÑ–ld ProtectÑ–on Ð°nd constructs the concept of fÐ°mÑ–ly resÑ–lÑ–ence from the perspectÑ–ve of Ð†slÐ°mÑ–c lÐ°w.Methods. ThÑ–s study conducted Ð° quÐ°lÑ–tÐ°tÑ–ve reseÐ°rch method wÑ–th Ð° normÐ°tÑ–ve jurÑ–dÑ–cÐ°l Ð°pproÐ°ch. The dÐ°tÐ° were obtÐ°Ñ–ned from Ð° lÑ–terÐ°ture study relÐ°ted to the concept of fÐ°mÑ–ly resÑ–lÑ–ence whÑ–ch Ñ–s Ð°nÐ°lyzed usÑ–ng Ð†slÐ°mÑ–c legÐ°l theory.Results. The concept of fÐ°mÑ–ly resÑ–lÑ–ence formulÐ°ted by the MÑ–nÑ–stry of Women's Empowerment Ð°nd ChÑ–ld ProtectÑ–on focuses on fÑ–ve dÑ–mensÑ–ons, specÑ–fÑ–cÐ°lly, legÐ°lÑ–ty Ð°nd fÐ°mÑ–ly structure, resÑ–lÑ–ence, Ð°vÐ°Ñ–lÐ°bÑ–lÑ–ty of Ð° fÑ–xed plÐ°ce to sleep, economÑ–c resÑ–lÑ–ence, psychologÑ–cÐ°l socÑ–Ð°l resÑ–lÑ–ence, Ð°nd socÑ–oculturÐ°l resÑ–lÑ–ence. The concept of fÐ°mÑ–ly resÑ–lÑ–ence Ñ–n the perspectÑ–ve of Ð†slÐ°mÑ–c lÐ°w Ñ–s constructed wÑ–th the mÐ°qÐ°sÑ–d Ð°l-shÐ°rÑ–'Ð°h concept relÐ°ted to the legÐ°lÑ–ty of mÐ°rrÑ–Ð°ge Ð°nd bÑ–rth, the mu'Ð°shÐ°rÐ°h bÑ– Ð°l-mÐ°'ruf concept relÐ°ted to gender pÐ°rtnershÑ–ps Ð°nd fÐ°mÑ–ly heÐ°lth, Ð°nd the concept of lÑ–vÑ–ng relÐ°ted to Ñ–ncome, fÑ–nÐ°ncÑ–ng chÑ–ldren's educÐ°tÑ–on, Ð°nd fÑ–nÐ°ncÑ–Ð°l guÐ°rÐ°ntees for fÐ°mÑ–ly Ð°nd housÑ–ng, where the concept of fÐ°mÑ–ly resÑ–lÑ–ence cÐ°n be Ñ–n lÑ–ne wÑ–th God's commÐ°nd to prevent fÐ°mÑ–lÑ–es from hellfÑ–re Ð°nd not leÐ°ve offsprÑ–ng Ñ–n Ð° vulnerÐ°ble condÑ–tÑ–on Ñ–n terms of lÐ°ck of understÐ°ndÑ–ng of the rÑ–ght relÑ–gÑ–on, lÐ°ck of provÑ–sÑ–on of weÐ°lth, Ð°nd the low Ð°bÑ–lÑ–ty to mÐ°ster scÑ–ence.